Effectiveness of stress management technique in learning an experimental & survey based research - Vigneswaran, Kannan (2017)
The aim of this study is to examine the “Effectiveness of Stress Management Technique in Learning”. Stress is a major element which affects one’s cognitive functions such as memory and attention span. Stress distinctly impairs memory retrieval and behavior, for instance the risk of underachieving in assessments. In having this thought, “Mindfulness” technique was used as the intervention or the stress management technique in this study. This is an experiment and survey based research which was conducted among 47 second and third year nursing students of International Medical College in Subang Jaya, Malaysia. Permission and consent were taken prior to the implementation of this research. This study includes total of 50 minutes of teaching of topic on Coaching and Mentoring which is segregated into Part A and B in order to measure the effectiveness of the Mindfulness on this study in a meritocratic manner. The effectiveness of “Mindfulness” was explored using three different instruments which are a) Multiple Choice Assessments, b) Self -Rating Stress Level Marker Scale and c) Mindfulness Stress Management Technique Satisfaction Survey. The researcher used quantitative research method to conduct this study. A pilot study was conducted before implementing the actual research. The study was analysed by using descriptive and inferential statistics which comprises of various frequency tables and charts. This study was carried out with the intention to give out a valuable method to the learners out there where they can reduce stress and also improve cognitive abilities which can result in optimum learning. The study is to benefit many educational stakeholders, policy makers in an educational setting, learners, educators as well as the general public.